2021
DOI: 10.19101/ijatee.2020.s1762116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influential factors of cybersecurity awareness in Malaysia during the pandemic outbreak: a structural equation modeling

Abstract: The advanced growth of communication technology today has brought great benefits to the people of Malaysia in many ways. One of those is the introduction of Society 5.0 concept, in which referring to smart cities which will solve future issues and challenges using digital approaches including artificial intelligence (AI), big data and Internet of Things (IoT). Big data collected by the various devices will be analysed and transformed into new type of innovation technologies by AI and will be beneficial for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Nevertheless, all the respondents were aware of cybercrimes, but they were not able to differentiate between the types of threats. Previous study by Wahid et al (2021) discussed that two out of three factors (social & individual) were found to be less significant towards cyber security awareness among respondents who aged between 50 and above 60. The current study and previous study by Wahid et al (2021) shows that more awareness on information security is needed to be emphasised among young Internet users.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, all the respondents were aware of cybercrimes, but they were not able to differentiate between the types of threats. Previous study by Wahid et al (2021) discussed that two out of three factors (social & individual) were found to be less significant towards cyber security awareness among respondents who aged between 50 and above 60. The current study and previous study by Wahid et al (2021) shows that more awareness on information security is needed to be emphasised among young Internet users.…”
Section: Resultsmentioning
confidence: 94%
“…Besides, there were no any research done in Malaysia to study the effect of age on information security awareness level among young Internet users. There was one study conducted among 300 senior adults aged from 50 until 60 and above to determine the information security awareness level (Wahid et al, 2021). Thus, this study is aimed to fill in the research gaps by studying effect of age on information security awareness level among young Internet users in Malaysia.…”
Section: Information Security Awarenessmentioning
confidence: 99%
“…These nine studies therefore explicitly or implicitly recognized the existence of those we refer to as QTIs. Older adults, especially those new to digital technology during the COVID-19 pandemic, are described as vulnerable to online privacy and data safety risks, including identity theft [63,65], data security breaches [6,7,31,33], scams [6,7,11,26,27,30,34,52,64], and other fraud [51]. Several articles specifically addressed mobile banking, including the perceived versus real risks of fraud, such as identity theft and data breaches [63,65,66].…”
Section: Characterization Of Quarantine Technology Initiates and Thei...mentioning
confidence: 99%
“…Several articles specifically addressed mobile banking, including the perceived versus real risks of fraud, such as identity theft and data breaches [63,65,66]. Additionally, multiple articles highlight an increase in cybercrime targeting older adults, with online fraud rates rising significantly during the pandemic [6,7]. One article, by Recupero, went as far as to highlight the limited research on technologyrelated risk factors correlated with financial abuse and claimed that these factors are likely to evolve over time, but stopped short of naming forced technology adoption as one of those potential risk factors [67].…”
Section: Characterization Of Quarantine Technology Initiates and Thei...mentioning
confidence: 99%
See 1 more Smart Citation